Exploring Diversity within Chytridiales and Rhizophydiales (Chytridiomycota) in Korea - Thuong T. T. Nguyen; Sun Jeong Jeon; Do Young Song; Dong Hee Kim; Hyang Burm Lee (Mycobiology)
Chytridiomycota is the most species-rich phylum of basal lineage fungi with a worldwide distribution. Its species constitute essential components of freshwater ecosystems. However, the diversity of this group in Korea remains understudied. A survey of Chytridiales and Rhizophydiales fungi was conducted in soil and freshwater environments in Korea, and seven strains were isolated. Based on morphological and molecular data, a previously unidentified, novel Rhizophydium species was discovered, designated Rhizophydium multiplex sp. nov. In addition, Chytriomyces hyalinus and Globomyces pollinis-pini were isolated for the first time in Korea. Detailed descriptions and illustrations of the three species are provided. This study highlights the potential diversity of chytrid fungi in Korea.